New combinations, sex association, behavioural notes and potential host record for two Neotropical species of Pseudomethoca Ashmead, 1896 (Hymenoptera: Mutillidae) - Bergamaschi, Antonio C. B.; Cambra, Roberto A.; Melo, Gabriel A. R. (Zootaxa, 2011)
The present paper transfers Mutilla pumila Burmeister, 1854 and Mutilla pergrata Cresson, 1902 to the genus Pseudomethoca Ashmead, and a lectotype is designated for Mutilla pumila. The male of this species, previously known only from the female sex, is described and the female is redescribed and illustrated for the first time. Sex association was based on laboratory mating trials. Field observations in a montane Atlantic forest site in southern Brazil provided us behavioural notes on attempts of parasitism in nests of the halictine bee Dialictus seabrai (Moure, 1956).